Steady state frequency response of STATCOM. - Mohaddes, M. (IEEE Transactions on power delivery)
The paper develops analytical expressions for the admittances and impedances of a static synchronous compensator (STATCOM) as a function of frequency. The expressions include the conventional positive and negative sequence admittance as well as transfer admittances where a positive sequence current generates a negative sequence voltage at another frequency. These results are then corroborated using the tool of electromagnetic transients simulation. The expressions are shown to be valid for six-pulse as well as higher pulse number configurations. The impact of the STATCOM's control system on the admittance is also investigated